Phenobarbital-induced autoimmune haemolytic anaemia, thrombocytopenia and peripheral lymphadenomegaly due to reactive lymphoid hyperplasia in a cat. Issue 1 (March 2022) - Walton-Clark, Michelle; Travail, Victoria; Best, Matthew
Case summary: A female neutered domestic longhair cat, aged 1 year and 5 months, presented with lymphadenomegaly and anaemia following therapy with phenobarbital for idiopathic epilepsy. Physical examination revealed pale pink mucous membranes and peripheral lymphadenomegaly. Haematology showed a regenerative anaemia (haematocrit 19.3%, reticulocyte count 118.08 ×10 9 /l), and saline agglutination was positive. Infectious disease screening was negative and lymph node cytology was consistent with reactive lymphoid hyperplasia. A diagnosis of phenobarbital-induced reactive lymphoid hyperplasia and immune-mediated anaemia was suspected. Complete resolution of the lymphadenomegaly and anaemia was documented within 4 weeks of phenobarbital discontinuation. Relevance and novel information: There are limited case reports of phenobarbital-induced haematological changes and lymphadenomegaly; however, the combination has not previously been reported in cats and is similar to the rare but significant syndrome in humans known as 'anticonvulsant hypersensitivity syndrome'. Anticonvulsant hypersensitivities should be considered as a potentially serious, yet reversible, sequela to phenobarbital treatment that may be mistaken for more severe illness such as neoplasia.